Genetic divergence of sweet potato genotypes based on morpho-agronomic traits - Oliveira,Darllan JLSF de (2021)
ABSTRACT Sweet potato is a vegetable of great importance in human consumption, due to its high nutritional value. It presents high phenotypic variation, with different forms of roots, leaves and vines. Given the above, we aimed to study the genetic divergence of sweet potato genotypes based on morpho-agronomic traits. The experiment was conducted in an experimental area of Unesp, Ilha Solteira Campus, located in Selvíria-MS. The experimental design used was randomized blocks with two replicates, including 200 genotypes and ‘Beauregard’ as a biofortified control. Shoot morphological traits of the genotypes were evaluated at 110 days and root morphological traits were evaluated at 127 days after planting. We used the obtained data to perform descriptive analysis, in percentage of phenotypic classes. In order to study genetic divergence, multivariate analysis was performed, grouping was done using Tocher’s and Ward’s methods. We also analyzed relative contribution of each trait for genetic divergence. Statistical analyzes were performed using Genes software and SAS. Wide genetic variability could be verified in the population studied in this experiment, being possible to obtain genetic gains in recombination between genotypes. Grouping using Tocher’s method was more effective for discriminating dissimilarity between genotypes. The low relative importance of leaf size, internode diameter and secondary peel color makes further evaluation of these traits unnecessary, reducing labor costs, cost and execution time.